KOMUNIKASI INTERPERSONAL KAUM LESBIAN DALAM BERINTERAKSI SOSIAL - Dekantari, Renanda Feby (JURNAL KOMUNITAS, 2018)
Lesbian is a social phenomenon that cannot be denied. The existence of lesbian is recognized as a reality in the society and raise various reaction from the surrounding area. The denial from the surrounding and wider area made the lesbian feel afraid, doubtful, and even ashamed to show their true sexual identity. Thus became a persecutor to communicate with the society. The communication involved between the lesbian and the society is not easy, it needs process that the communication can be done and in the end the lesbian existence can be admitted or accepted by the surrounding area in such way that create the mutual understanding communication. To get the admission of their existence as a lesbian in the surrounding society, the lesbian have to get involved in personal communication process. When the lesbian stated their selves and interact through interpersonal communication, certainly there is a distinctive pressure in deciding what will be stated and what should be under the rose. The research concerning lesbian interpersonal communication in â€œBelokâ€ community at Solo City is a descriptive qualitative research. The process in conducting this research emphasized in qualitative research. In order to be done further, this research was focused on the symbolic interaction done by the lesbian about their selves and then observes how the lesbian community interacts with the surrounding society which is formed into their interpersonal communication using socio-cultural method